2016
DOI: 10.1080/00325899.2016.1242880
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear behaviours of surface densified powder metallurgy Fe–2Cu–0.6C material

Abstract: Surface rolling was employed to fabricate a densified layer on a powder metallurgy (PM) Fe-2Cu-0.6C piece. A densified surface layer with a depth of 335 μm and a surface hardness of 330 HV 0.1 was obtained, in which the lamellar spacing of pearlite and grain size of ferrite were refined. Friction and wear behaviours of the surface densified material were studied. Results indicated that friction coefficient of the rolled material decreased as the load increased, which was lower than that of the un-rolled materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This indicates that the addition of carbon improves the friction performance of the densified layer in PM parts and is conducive to extending the service life of parts in actual working situations. The surface-densified layer, with relatively high hardness, could hinder crack initiation and propagation on and under the surface and enhance the wear properties of the PM material [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that the addition of carbon improves the friction performance of the densified layer in PM parts and is conducive to extending the service life of parts in actual working situations. The surface-densified layer, with relatively high hardness, could hinder crack initiation and propagation on and under the surface and enhance the wear properties of the PM material [6].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with forging, the advantages of the PM process are that it is suitable for complexly shaped parts, the raw material utilization rate is high, and the production cost is reduced [3,4]. However, the inherent porosity in traditional single pressed and sintered products is one of the major factors causing reduction in the mechanical properties of PM parts [5,6]. Although new advances in powder metallurgy such as hot isostatic pressing (HIP), selective laser melting (SLM), and high-velocity compaction technology are used to manufacture high-performance components with homogeneous high density, the facilities required for these processes are more specialized and the production costs are higher compared with those of the surface rolling process [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those studies indicated that a densification depth of 0.2-1 mm was formed on the surface layer with an obvious increase in density and surface hardness. The fatigue and wear resistance of the PM gears treated by surface densification can also be enhanced [16,17]. These reports emphasize the increased performance after rolling, although few address the warm rolling surface densification process on PM materials.…”
Section: Introductionmentioning
confidence: 96%